X-linked ADGRG2 mutation and obstructive azoospermia in a large Pakistani family. Issue 1 (December 2018) - Khan, Muhammad; Pollock, Nijole; Jiang, Huaiyang; Castro, Carlos; Nazli, Rubina; Ahmed, Jawad; Basit, Sulman; Rajkovic, Aleksandar; Yatsenko, Alexander
Abstract We performed whole exome sequencing to identify an unknown genetic cause of azoospermia and male infertility in a large Pakistani family. Three infertile males were subjected to semen analysis, hormone testing, testicular histology, ultrasonography, karyotyping, Y-chromosome microdeletion andCFTR testing. The clinical testing suggested a diagnosis of obstructive azoospermia (OA). To identify the cause, we performed whole exome sequencing (WES) for 2 infertile brothers and 2 fertile family members. For segregation analysis and variant confirmation, we performed Sanger sequencing. WES data analysis of the family revealed segregated variants in 3 candidate genes. We considered novel nonsense variant c.2440C > T(p.Arg814*) in X-linked geneADGRG2 as biologically most plausible. It is predicted to truncate the protein by 204 amino acids (aa) at a key transmembrane domain.Adgrg2 -knockout male mice show sperm loss due to obstructive fluid stasis, whileADGRG2 mutations cause OA in the infertile male patients. Our analysis of testicular histology reveals secondary severe reduction of spermatogenesis, consistent with human and knockout mouse phenotypes. TheADGRG2 nonsense mutation is absent in the largest population databases, ExAC and gnomAD. Analysis of the novel nonsense mutation in extended family members confirmed co-segregation of the mutation with OA in all affected males. The likely pathogenic nature of the mutation is supported by its truncation effect on the transmembrane domain and distinctive ultrasound results. The study demonstrates effectiveness of WES in discovering a genetic cause of azoospermia.